Assessment of water quality and trophic state using a multipara-metric index-based approach for Lake Guineo, Lake Carraizo and Lake Cidra, Puerto Rico - Gladys Noelia Benitez (Journal of Bioresources and Environmental Sciences, 2024)
To ensure a safe drinking water supply, it is necessary to protect water quality. The proposed project aims to understand water quality data analyzed from a temporal and spatial perspective on the following physiochemical parameters: DO, pH, temperature, Secchi disc turbidity, conductivity, nitrate, chlorophyll α & phosphate. The results provide information to evaluate the status of the water quality and its suitability for human consumption. These variables related to the general characteristics of water quality and trophic level were used for calculation of a water quality index (WQI) and trophic state index (TSI) to assess 3 lakes in Puerto Rico: Lake Cidra, Lake Carraizo and Lake Guineo. Presence or absence of macrophytes were monitored during six months in the three reservoirs in Puerto Rico as well as the parameters mentioned above. The objective of this investigation is to discuss the trophic state and water quality in 3 different trophic state reservoirs in Puerto Rico. Results were correlated with the density of the macrophyte species, Eichhornia crassipes. Variations of water in situ multiparametric sampling were recorded for 6 months. Thus, integrating components that define the status of reservoirs using multiparameter measurements from various perspectives; a better diagnosis is expected regarding the water quality assessment. This investigation aims to undertake a comprehensive study of water quality by implementing the WQI and TSI indices, considering physical, chemical, and biological parameters with respect to eutrophication and ecological considerations for three reservoirs in the Puerto Rico, providing information regarding the quality of water and trophic state of the chosen reservoirs. Overall WQI results revealed that the water quality improved after the Hurricane Fiona’s occurrence. Trophic State Index after the hurricane showed slight fluctuations in the reservoirs.